Na+, K+-ATPase inhibition induces neuronal cell death in rat hippocampal slice cultures: Association with GLAST and glial cell abnormalities - Yuki Kurauchi; Kazuki Noma; Akinori Hisatsune; Takahiro Seki; Hiroshi Katsuki (Elsevier, 2018)
Na+, K+-ATPase is a highly expressed membrane protein. Dysfunction of Na+, K+-ATPase has been implicated in the pathophysiology of several neurodegenerative and psychiatric disorders, however, the underlying mechanism of neuronal cell death resulting from Na+, K+-ATPase dysfunction is poorly understood. Here, we investigated the mechanism of neurotoxicity due to Na+, K+-ATPase inhibition using rat organotypic hippocampal slice cultures. Treatment with ouabain, a Na+, K+-ATPase inhibitor, increased the ratio of propidium iodide-positive cells among NeuN-positive cells in the hippocampal CA1 region, which was prevented by MK-801 and d-AP5, specific blockers of the N-methyl-d-aspartate (NMDA) receptor. EGTA, a Ca2+-chelating agent, also protected neurons from ouabain-induced injury. We observed that astrocytes expressed the glutamate aspartate transporter (GLAST), and ouabain changed the immunoreactive area of GFAP-positive astrocytes as well as GLAST. We also observed that ouabain increased the number of Iba1-positive microglial cells in a time-dependent manner. Furthermore, lithium carbonate, a mood-stabilizing drug, protected hippocampal neurons and reduced disturbances of astrocytes and microglia after ouabain treatment. Notably, lithium carbonate improved ouabain-induced decreases in GLAST intensity in astrocytes. These results suggest that glial cell abnormalities resulting in excessive extracellular concentrations of glutamate contribute to neurotoxicity due to Na+, K+-ATPase dysfunction in the hippocampal CA1 region. Keywords: Glutamate aspartate transporter (GLAST), Hippocampus, Na+, K+-ATPase, Neuronal cell death, N-methyl-d-aspartate (NMDA) receptor